Factores ambientales y su incidencia en la insuficiencia respiratoria aguda en menores de 5 años de la ciudadela Barrio Lindo Babahoyo Los Ríos periodo septiembre 2017 a febrero 2018 - Lema Cortez, Diana Elizabeth (2018)
Acute respiratory infections are defined as the set of communicable diseases of the respiratory system that includes from the common cold to pneumonia. Acute respiratory infections are the most frequent cause in pediatric consultations, with children under 5 years of age being the most vulnerable. These are present throughout the year as there are multiple factors that produce them, such as environmental pollution, type of climate among others. The objective of this research was to identify environmental factors that affect acute respiratory infection in patients under 5 years of age in the Barrio Babahoyo Los Ríos neighborhood from September 2017 to February 2018. A descriptive and exploratory study was conducted to identify environmental factors that affect acute respiratory infection. For the collection of data, the interview, a survey and a survey addressed to the mothers of children under 5 years of the Barrio Lindo Citadel were used. As an instrument, a questionnaire was made where the different variables object of research were explored, our population It was 80 children and the sample was 35 children who suffered from IRA in the first semester of 2017 which were chosen using the inclusion, exclusion and exit criteria. With this research it was possible to determine that the children who suffered most from IRA were those from 3 to 4 years of age, of rural.